Gut Fungal Microbiome Responses to Natural Cryptosporidium Infection in Horses - Wang, Yaping; Li, Xuwen; Chen, Xiushuang; Kulyar, Muhammad Fakhar-e-Alam; Duan, Kun; Li, Huade; Bhutta, Zeeshan Ahmad; Wu, Yi; Li, Kun (Frontiers in Microbiology, 2022)
It is critical to characterize changes in the structure and composition of the host fungal community in natural Cryptosporidium infection, given the possible significance of the gut microbiome in host homeostasis and disease progression. A total of 168 rectal fecal samples were collected and examined using nPCR; positively infected samples were double-checked using 18S rDNA high-throughput sequencing. After confirming positive samples, ITS high-throughput sequencing was utilized to investigate the fungal community's responses to natural Cryptosporidium infection. Results showed that a total of three positive samples (1.79%) were identified with an increased abundance of fungi associated with health hazards such as class Dothideomycetes, families i.e., Cladosporiaceae, Glomerellaceae and genera i.e., Wickerhamomyces, Talaromyces, Cladosporium, Dactylonectria, Colletotrichum. On the other hand, taxa associated with favorable physiological effects on the host were shown to have the reverse impact such as families i.e., Psathyrellaceae, Pseudeurotiaceae) and genera (Beauveria, Nigrospora, Diversispora). For the first time, we evaluated the condition of natural Cryptosporidium infection in horses in Wuhan, China, and discovered distinct variations in the fungal microbiome in response to natural infection. It might prompt a therapy or prevention strategy to apply specific fungal microorganisms that are probably responsible for decreased susceptibility or increased resistance to infection.